2021
DOI: 10.1080/19491034.2021.1910437
|View full text |Cite
|
Sign up to set email alerts
|

4DNvestigator: time series genomic data analysis toolbox

Abstract: Data on genome organization and output over time, or the 4D Nucleome (4DN), require synthesis for meaningful interpretation. Development of tools for the efficient integration of these data is needed, especially for the time dimension. We present the ‘4DNvestigator’, a user-friendly network-based toolbox for the analysis of time series genome-wide genome structure (Hi-C) and gene expression (RNA-seq) data. Additionally, we provide methods to quantify network entropy, tensor entropy, and statistically significa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 31 publications
(46 reference statements)
1
23
0
Order By: Relevance
“…This approach is useful for quantifying differences between maternal and paternal genomes throughout the cell cycle, highlighting gene sets with large structural or expression differences over time. In previous work, we have also shown that this method may be broadly applicable to time-series analysis of different cell types ( Lindsly et al., 2021 ).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…This approach is useful for quantifying differences between maternal and paternal genomes throughout the cell cycle, highlighting gene sets with large structural or expression differences over time. In previous work, we have also shown that this method may be broadly applicable to time-series analysis of different cell types ( Lindsly et al., 2021 ).…”
Section: Resultsmentioning
confidence: 89%
“…These matrices represent the local genomic structure of the differentially expressed genes, and are slightly smaller than average TAD size ( ∼ 1 Mb). We then compared the correlation matrices of the log 2 -transformed local Hi-C data and determined whether or not the matrices have statistically significant differences (p < 0.05) ( Koziol et al., 1997 ; Lindsly et al., 2021 ). We applied this comparison to all genes that were differentially expressed in RNA-seq (Bru-seq) and found that 515 (403) genes had at least one comparison in which both the expression and local structure had significantly changed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations